Evaluating CO2 calculation error from organic alkalinity and pH measurement error in low ionic strength freshwaters. (12th September 2020) - Liu, Shaoda; Butman, David E.; Raymond, Peter A.
Abstract: Dissolved CO2 concentration calculated from historical or in situ alkalinity and pH measurements according to carbonate equilibria is widely applied in freshwater CO2 studies yet there is long concern on systematic errors associated with the calculation. Correction of the CO2 calculation errors is however hampered by a lack of correct understandings of error sources and magnitudes. Here through reviewing literature quantification of the effect, we point out pH measured by commercial glass electrodes is not reliable and biased unidirectionally toward lower values by −0.14 ± 0.20 on average. This effect, together with high organic alkalinity, is responsible for unreliable CO2 calculations in low ionic strength freshwaters. Relying on a series of interdependencies between freshwater properties, the analysis further proposes a roadmap for correction of the errors. The method, when testing against a dataset of direct CO2 measurements, is proved effective at reducing CO2 calculation errors. The analysis represents a significant progress in freshwater CO2 studies based on carbonate equilibria and future applications of the method are advised to apply the corrections to freshwaters of <1000  μ eq L −1 in total alkalinity.